Textbook of Aramaic ostraca from Idumea. - Porten, Bezalel; Porten, Bezalel; Yardeni, Ada; Yardeni, Ada; Kletzing, Matt; Han, Eugen (Eisenbrauns, 2020)
Since the early 1990s, about two thousand Idumean Aramaic ostraca have found their way onto the antiquities market and are now scattered across a number of museums, libraries, and private collections. This multivolume textbook classifies these ostraca according to subject matter and brings them together into a single publication. With this fourth installment, Bezalel Porten and Ada Yardeni continue their comprehensive edition of Aramaic ostraca from Idumea. Volumes 1-3 published and cataloged 255 Personal Name Dossiers containing 1,152 texts. Volume 4 contains 377 texts divided into six dossiers, including 54 payment orders, 77 accounts, 74 workers texts, 62 names, 87 jar inscriptions, and 23 letters. The payment orders document officially authorized transfers of goods, while the accounts show how those goods were inventoried. The workers texts illustrate the distribution and supply of laborers, the name lists show people as individuals, and the jar inscriptions track vessels in motion. Color photographs, ceramic descriptions, hand-copies, transcriptions, translations, and commentaries are provided for the texts, along with figures and tables, and introductions and summaries of each dossier.A unique source for the onomastics and social and economic history of fourth-century Idumea--and, by extension, of Judah--this multivolume work will become the primary resource for information on these texts.